Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Fakultas Ekonomi & Bisnis Universitas Islam Sumatera Utara Untuk Membangun Wirausaha - Tuti Anggraini (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2020)
This study aims to analyze the influence of product development variables, market expansion and market share on the potential of sharia insurance in North Sumatra Province, and also to establish a development strategy model in the Sharia insurance industry. This research uses quantitative descriptive statistic research approach and also strategy development approach with SWOT analysis model. The population in this study is the people of North Sumatra with the model of withdrawal of stratfikasi samples by taking several districts / cities in the Province of North Sumatra, namely Medan, Binjai, Deli Serdang, Sibolga, Pematang Siantar and Padangsidempuan. Product development variable regression coefficient of 0.469; this means that if the insurance company develops the product will experience an increase of one unit, then the potential of sharia insurance will increase by 0.469 units The coefficient of variable regression of market expansion is 0.892; this means that if the market share increases by one unit, the potential meal of Sharia insurance will increase by 0.892 units The coefficient of variable regression of market share is 0.048; this means that if the market share increases by one unit, The Potential meal will increase by 0.048 units assuming other independent variables of fixed value. Sharia insurance product development strategy model in North Sumatra with SWOT analysis approach is located in Quadrant 1 (Aggressive). Where it has a good value weight in the internal environment at the position of strength (Strength) and the weight of value in the external environment is good at the position of opportunity (Opportunity). It can be concluded that if the SWOT diagram is in quadrant 1 (Aggressive), it shows sharia insurance companies in northern Sumaetra Province have opportunities and many forces that encourage the use of these opportunities. Quadrant 1 supports an aggressive growth oriented strategy.